Cookies Kaya Serat Pangan dengan Bahan Dasar Tepung Asia (Ampas) Ubi Jalar - Tjahja Muhandri; Disty Septieni; Subarna Subarna; Sutrisno Koswara; Dase Hunaefi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2018)
Sweet Potato Asia Fluor (SPAF) is a by product from starch extraction that contain high level of dietary fiber. In this present studies, this flour (by product) was applied in cookies production as a wheat flour replacer. The aim of the research was to study cookies formulation using sweet potato asia flour in cookies production compliance claiming of high level of dietary fiber. The formulations were fixed using 100 gram of SPAF but with different amount of margarine (75, 65 dan 55% of 100 gram of SPAF) and egg yolk (16, 14, dan 12% of 100 gram SPAF). Dough bulk density, product bulk density, expansion ratio, texture, and pores structure, and also hedonic’s rating test were performed to analyse the cookies quality physically. Selected formula from hedonic test was analized proximate, dietary fiber and AKG. The higher concentration egg yolk and margarine in dough, the lower dough and cookies’ density, and the lower hardness. The selected formula based on sensory evaluation was egg yolk 12% and margarine 55 %. In 20 grams serving size, cookies contained total energy 101kcal, 1% RDA of protein, 9% RDA of fat, 4% RDA of carbohydrate, and 5% RDA of dietary fiber based on a 2150 kcal diet. The selected formula had 6.5% dietary fiber in which comply to the BPOMN regulation of claiming high in dietry fiber (minimum 6%).